A humanistic gift from the Brazilian Emperor D. Pedro II (1825 - 1891) to the Brazilian nation: the first lunatic asylum in Latin America Um presente humanitário do Imperador D. Pedro II (1825 - 1891) à nação brasileira: o primeiro asilo para lunáticos da América Latina - Antonio E. Nardi; Adriana Cardoso Silva; Jaime E. Hallak; José A. Crippa (Arquivos de Neuro-Psiquiatria, 2013)
Until the beginning of the 19th century, psychiatric patients did not receive specialized treatment. The problem that was posed by the presence of psychiatric patients in the Santas Casas de Misericórdia and the social pressure from this issue culminated in a Decree of the Brazilian Emperor, D. Pedro II, on July 18, 1841. The “Lunatic Palace” was the first institution in Latin America exclusively designed for mental patients. It was built between 1842 and 1852 and is an example of neoclassical architecture in Brazil, located at Saudade Beach in the city of Rio de Janeiro. In the 1930s and 1940s, the D. Pedro II Hospital was overcrowded, and patients were gradually transferred to other hospitals. By September of 1944, all the patients had been transferred and the hospital was deactivated. Key words: psychiatry, history, madness. Até o início do século 19, os pacientes psiquiátricos não recebiam nenhum tipo de tratamento específico. A pressão social da época decorrente do problema representado pela presença dos pacientes psiquiátricos nas Santas Casas de Misericórdia culminou no Decreto do Imperador brasileiro, D. Pedro II, em 18 de julho de 1841. O “Palácio dos Loucos” foi a primeira instituição na América Latina voltada exclusivamente para a assistência aos doentes mentais. Foi construído entre 1842 e 1852, na Praia da Saudade na cidade do Rio de Janeiro, e é um dos expoentes da arquitetura neoclássica do Brasil. Nas décadas de 1930 e 1940, o então Hospital D. Pedro II estava superlotado, tendo sido os pacientes gradualmente transferidos para outros hospitais. Em setembro de 1944, concluiu-se a tranferência de todos os pacientes e o hospital foi desativado.